Boerhavia diffusa and Coccinia grandis: Two indigenous vegetables as a source of essential minerals, vitamins, amino acids, and fatty acids - Shyama Prosad Moulick; Farhana Jahan; Md. Zia Uddin Al Mamun; Md. Imam Sohel Hossain; Khondoker Shahin Ahmed; Md. Alamgir Kabir; Md. Mamunur Rashid; Rahima Akter Sathee; Muhammad Mahfuz Hasan (Applied Food Research)
Since the nutritional makeup of many plants is still unknown, people have historically included them in their diets without even being aware of their health advantages. Therefore, the present study aimed to uncover the proximate composition, minerals, vitamins, amino acids, and fatty acids composition of two locally consumed vegetables, namely Boerhavia diffusa and Coccinia grandis. From the analysis, these vegetables had a significant protein, fat, and carbohydrate content. Regarding mineral contents, both plants had a great amount of potassium, calcium, iron, sodium, and zinc. These vegetables had a remarkable content of vitamins such as B1, B2, B3, B5, B6, and C. The leaves of both plants had important essential amino acids such as leucine, lysine, and phenylalanine, as well as non-essential amino acids. Unsaturated fatty acids such as linolenic acid, linoleic acid, and erucic acid were more prominent in Coccinia grandis than Boerhavia diffusa. In addition, both plants had a significant amount of saturated fatty acids such as palmitic acid, stearic acid, and lauric acid. Thus, it can be concluded that these two vegetables have magnificent profiles of nutrients which could make them as important sources of minerals, vitamins, and fatty acids.